Phenotypic and genetic parameter estimates of factors related to the performance of trypanotolerant livestock - Trail, J.C.M.; D'Ieteren, G.D.M. (Food and Agriculture Organization of the United Nations, 1992)
Considerable progress has been made in defining and measuring criteria of trypanotolerance since the late 1970's, when ILCA, FAO and UNEP worked with researchers in 18 West and Central African countries to show clear relationship between level of trypanosomiasis risk and animal performance. During 1980's, work with NDama cattle at sites of the African Trypanotolerant Livestock Network quantified the effects of ability to control to Development of anaemia on a number of cattle performance traits. Results showed that packed red cell volume (PCV) values when parasitaemic were closely related to animal performance, and could be measured satisfactorily in one-year-old calves. As PCV values had higher heritabilites than, and positive correlations with, growth, there appeared to be definite possibilities for selection of trypanotolerant animals on the basis of control of anaemia Development. In contrast during the 1980's, the degree of parasitaemia could not be so accurately quantified using the buffy coat technique available for field use. So, in 1990 antigen-detection enzyme immunoassays (anti-ELISA) developed at ILRAD were utilized. Early results showed that the antigen-ELISA is significantly more sensitive in monitoring Trypanosoma congolense and T. vivax infections and has the potential to increase the efficacy of selection of trypanotolerant N'Dama cattle under tsetse challenge in the field in trhee main ways.